2021
DOI: 10.1016/j.xcrm.2021.100250
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Brugada syndrome loci reveals that fine-mapping clustered GWAS hits enhances the annotation of disease-relevant variants

Abstract: Summary Genome-wide association studies (GWASs) are instrumental in identifying loci harboring common single-nucleotide variants (SNVs) that affect human traits and diseases. GWAS hits emerge in clusters, but the focus is often on the most significant hit in each trait- or disease-associated locus. The remaining hits represent SNVs in linkage disequilibrium (LD) and are considered redundant and thus frequently marginally reported or exploited. Here, we interrogate the value of integrating the full s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 111 publications
(229 reference statements)
3
14
0
Order By: Relevance
“…We have observed that the twenty-two heterozygous sites are split by major and minor allele frequencies, with all major alleles in one chromosomal copy and all minor alleles in the other chromosomal copy. This finding builds upon the previously proposed model that the 13 kb Hap1/Hap3 region represents Ying-Yang haplotypes 44 . To generate SCN10A amplicons, genomic DNA was extracted with the same modified salting-out method used to isolate the ∼20 kb T1-T4 targets ( Fig.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…We have observed that the twenty-two heterozygous sites are split by major and minor allele frequencies, with all major alleles in one chromosomal copy and all minor alleles in the other chromosomal copy. This finding builds upon the previously proposed model that the 13 kb Hap1/Hap3 region represents Ying-Yang haplotypes 44 . To generate SCN10A amplicons, genomic DNA was extracted with the same modified salting-out method used to isolate the ∼20 kb T1-T4 targets ( Fig.…”
Section: Resultssupporting
confidence: 87%
“…Fig. 6B ) 44 . Intriguingly, we observed a slight haplotype bias in our tests with blood-derived samples (Hap1>Hap3), which we did not observe when amplifying the 13 kb fragment from HG001 (compare allele burden plots between Suppl.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations